2022
DOI: 10.3389/fcell.2022.997028
|View full text |Cite
|
Sign up to set email alerts
|

Microglia modulate proliferation, neurite generation and differentiation of human neural progenitor cells

Abstract: Microglia, the primary immune cells of the brain, significantly influence the fate of neurons after neural damage. Depending on the local environment, they exhibit a wide range of phenotypes, including patrolling (naïve), proinflammatory, and anti-inflammatory characteristics, which greatly affects neurotoxicity. Despite the fact that neural progenitor cells (NPCs) and hippocampal neurons represent cell populations, which play pivotal role in neural regeneration, interaction between microglia and these cell ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Based on the differentiation protocol described previously [ 36 ] and used several times in our laboratory [ 37 , 41 , 42 , 43 ], we first created neural progenitors from an iPSC line of a healthy donor individual. Among the neural progenitor markers, SRY-box transcription factor 2 (SOX2) and Nestin were used to characterize NPCs.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the differentiation protocol described previously [ 36 ] and used several times in our laboratory [ 37 , 41 , 42 , 43 ], we first created neural progenitors from an iPSC line of a healthy donor individual. Among the neural progenitor markers, SRY-box transcription factor 2 (SOX2) and Nestin were used to characterize NPCs.…”
Section: Resultsmentioning
confidence: 99%
“…14,114 As the profiles of microglia increasingly favor the M2 state, they begin performing neuroprotective functions such as inactivating inflammation, promoting remyelination, repairing the BBB, and facilitating neural regeneration and neurite outgrowth. 115 The population expansion of microglia observed in preclinical animal models has parallels in humans. Human studies performed using CSF and peripheral blood samples from patients with SAH identified low numbers of microglia immediately after SAH, which progressively increased during the DCI period.…”
Section: Microglia In Delayed Cerebral Ischemiamentioning
confidence: 99%
“…In support of this, a study by Popova et al [ 204 ] showed that microglia could induce transcriptional changes in neural stem cells and reduce interferon signaling response genes, while interferon-induced transmembrane protein 3 (IFITM3) was previously shown to upregulate γ-secretase activity to increase Aβ production. By co-culturing activated microglia with NPC, Lilienberg et al [ 67 ] demonstrated that naïve microglia do not affect the proliferation of NPCs and enhanced neurosynaptic growth. Using this co-culture system, the authors also observed that the nitro blebbistatin-triggered synaptic development was enhanced by naïve microglia.…”
Section: Contributions Of Stem Cell Technology To Ad Research and Tre...mentioning
confidence: 99%
“…Using this co-culture system, the authors also observed that the nitro blebbistatin-triggered synaptic development was enhanced by naïve microglia. [ 67 ]. Popova et al [ 204 ] showed that microglia can induce transcriptional changes in neural stem cells and accelerate the emergence of synchronized oscillatory network activity in brain organoids, which has implications for the integration of stem cells into the original neural network following transplantation.…”
Section: Contributions Of Stem Cell Technology To Ad Research and Tre...mentioning
confidence: 99%